2000
DOI: 10.3109/07357900009012171
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Family Expression in Human Breast Cancer: Interleukin-1 Receptor Antagonist

Abstract: We hypothesize that interleukin-1 alpha, beta, and receptor antagonist (IL-1 alpha, IL-1 beta, and IL-1 ra, respectively) are present and tumor cell associated in human breast cancer (HBC). We believe the levels of these cytokines in breast tumor homogenates relate to other known prognosticators of patient survival (i.e., estrogen receptor [ER] status). Our results demonstrated that, immunohistochemically, tumor cells express IL-1 alpha, IL-1 beta, and IL-1 ra in most specimens tested. In breast tissue homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 22 publications
4
51
0
Order By: Relevance
“…In vitro studies have shown that IL-1 can inhibit malignant cell growth by affecting DNA synthesis (Shen et al, 2002). In human BC, IL-1 is involved in local regulation of tumor growth, angiogenesis, proliferation, and tumor attack (Miller et al, 2000;Pantschenko et al, 2003;Singer et al, 2003). IL-1a may also affect the risk of BC by regulating cell proliferation through a Ca 2+ / calmodulin-dependent pathway (Inokuchi et al, 1995), considering that breast calcification is a key risk factor for BC (Tse et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that IL-1 can inhibit malignant cell growth by affecting DNA synthesis (Shen et al, 2002). In human BC, IL-1 is involved in local regulation of tumor growth, angiogenesis, proliferation, and tumor attack (Miller et al, 2000;Pantschenko et al, 2003;Singer et al, 2003). IL-1a may also affect the risk of BC by regulating cell proliferation through a Ca 2+ / calmodulin-dependent pathway (Inokuchi et al, 1995), considering that breast calcification is a key risk factor for BC (Tse et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 ra levels correlate directly with the presence of estrogen receptors in breast cancers. Because IL-1, which is induced by TGF-␤ in wounded keratinocytes (59), is also associated with estrogen receptor-negative, poor prognosis cancers (60), the down-regulation of IL-1 ra might be permissive for IL-1 actions.…”
Section: Tgf-␤ Enhances Smad-dependent Transcription and Differentialmentioning
confidence: 99%
“…In human breast cancer, an important role of IL-1 and IL-1RA expression was noted in various studies (5 -7). These studies suggest that the IL-1 system is vital in the local control of tumor growth (6), important in regulating ''protumorigenic'' activities within the tumor microenvironment (7), and contributes to angiogenesis, tumor proliferation, and tumor invasion (5).…”
mentioning
confidence: 99%